KOMPENSASI NONFINANSIAL DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KOTA TERNATE - Widya Sariati; Nurlaila Nurlaila; Ruslan Kamis (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2020)
Objective: The purpose of this study are: (1) Knowing and analyzingthe influence of non-financial compensation on employeeperformance; (2) Knowing and analyzing the influence of jobsatisfaction on employee performance; and (3) Knowing andanalyzing the effect of non-financial compensation and jobsatisfaction on the performance of employees at the RegionalDisaster Management Agency of Ternate City. The number ofresearch samples was 36 employees at the Regional DisasterManagement Agency of Ternate City.Methodology: The test equipment used is multiple linear regressionanalysis (multiple regression) using statistical package for socialscientists (SPSS) as a statistical test tool.Finding: H1, H2, and H3 are accepted at the 5% confidence level.Conclusion: The results showed that: nonfinancial compensationhad a positive and significant effect partially on employeeperformance; Job satisfaction has a positive and significant effectpartially on employee performance; and nonfinancial compensationand job satisfaction simultaneously have a positive and significanteffect on employee performance. This shows that, nonfinancialcompensation and job satisfaction are able to improve theperformance of employees in the Office of the Regional DisasterManagement Agency of Ternate City.